2015
DOI: 10.1177/0300985815579994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity and Obesity-Related Molecules on Canine Mammary Gland Tumors

Abstract: Obesity can affect the clinical course of a number of diseases, including breast cancer in women and mammary gland tumors in female dogs, via the secretion of various cytokines and hormones. The objective of this study was to examine the expression patterns of obesity-related molecules such as aromatase, leptin, and insulin-like growth factor 1 receptor (IGF-1 R) in canine mammary carcinomas (CMCs) on the basis of the body condition score (BCS). Comparative analyses of the expression of these molecules, togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 43 publications
2
37
1
Order By: Relevance
“…In veterinary medicine, two recent studies demonstrated IGF-1 receptor expression and its role in canine osteosarcoma (Maniscalco et al 2015) and mammary gland carcinoma (Lim et al 2015). However, in our study, a single intramuscular PRGF or HPRGF injection at clinical doses did not result in an increase in circulating IGF-1 levels in any of the test periods.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In veterinary medicine, two recent studies demonstrated IGF-1 receptor expression and its role in canine osteosarcoma (Maniscalco et al 2015) and mammary gland carcinoma (Lim et al 2015). However, in our study, a single intramuscular PRGF or HPRGF injection at clinical doses did not result in an increase in circulating IGF-1 levels in any of the test periods.…”
Section: Discussioncontrasting
confidence: 80%
“…Regarding systemic effects of growth factors, some authors (Grimberg and Cohen 2000;Grimberg 2003;Renehan et al 2004;Lim et al 2015;Maniscalco et al 2015) reported in human and veterinary patients positive associations between high circulating levels of IGF-1 and risk for different types of cancer, as well as an ergogenic effect, taking part of the prohibited list of substances of the World Anti-Doping Agency (WADA).…”
Section: Introductionmentioning
confidence: 99%
“…Canine mammary tumor has also generated considerable attention as a translational model for human breast cancer 1 . Age, heredity, hormones, and obesity are reportedly risk factors of breast cancer 2, 3 , and surgical resection remains the first choice for mammary tumor therapy. However, for infiltrative and metastatic cases, adjuvant chemotherapy using agents such as doxorubicin and carboplatin; or radiation therapy are performed 4, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Very little information is available regarding Arom in the canine mammary gland (Marinelli et al 2004;Sanchez-Archidona et al 2007;Lim et al 2015).…”
Section: Introductionmentioning
confidence: 99%